The Influence of Flashcard Learning Media on the Beginning Reading Ability of Children Aged 5-6 Years at the Friends of Rina Medan Kindergarten - Gulo, Irene Elfrida; Simaremare, Aman (Asian Journal of Applied Education (AJAE), 2024)
In this research, the problem is that children's initial reading abilities are still low. This research aims to determine the effect of using flashcard media on the beginning reading abilities of children aged 5-6 years at the Sahabat Rina Medan Kindergarten. This research uses an experimental method approach (Quasi-experiment design) in the form of The One Group Pretest-Posttest Design. The population in this study were all students aged 5-6 years in class B2 with a sample size of 20 children at the Sahabat Rina Medan Kindergarten. The data collection instrument in this research used a performance test. From the data analysis, the pretest data (before treatment) has an average score (mean) of 26.90 and the posttest data (after treatment) has an average score (mean) of 37.95. Based on data analysis through non-parametric hypothesis testing, the SPSS 25 statistical test was obtained, namely 0.000. Therefore, it can be concluded that the use of flashcard media has a significant influence on the beginning reading abilities of children aged 5-6 years at Sahabat Rina Kindergarten.